2016
DOI: 10.1038/srep21613
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of ligand-induced activation of angiotensin II type 1 receptor signaling by the type 2 receptor via protein kinase C

Abstract: Angiotensin II (AII) type 2 receptor (AT2R) negatively regulates type 1 receptor (AT1R) signaling. However, the precise molecular mechanism of AT2R-mediated AT1R inhibition remains poorly understood. Here, we characterized the local and functional interaction of AT2R with AT1R. AT2R colocalized and formed a complex with AT1R at the plasma membrane, even in the absence of AII. Upon AII stimulation, the spatial arrangement of the complex was modulated, as confirmed by Förster resonance energy transfer (FRET) ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…This notion is supported by our recent FRET studies in HEK cells expressing AT 2 R and MasR that their agonists alone do not affect FRET suggesting that these ligands do not promote or dissociate dimerization. 29 Along the same line of notion, other studies suggested that pretreatment of agonist or antagonist did not affect interactions of AT 2 R with AT 2 R, 36 AT 1 R 40 or B 2 R. 41 …”
Section: Discussionmentioning
confidence: 80%
“…This notion is supported by our recent FRET studies in HEK cells expressing AT 2 R and MasR that their agonists alone do not affect FRET suggesting that these ligands do not promote or dissociate dimerization. 29 Along the same line of notion, other studies suggested that pretreatment of agonist or antagonist did not affect interactions of AT 2 R with AT 2 R, 36 AT 1 R 40 or B 2 R. 41 …”
Section: Discussionmentioning
confidence: 80%
“…5 The AT2R receptor stimulates various signaling pathways, which can be categorized into 3 broad types: regulation of protein phosphorylation, activation of phospholipases, and regulation of NO/cyclic guanosine monophosphate (cGMP). [25][26][27][28] Thus, the depressor phase may be due to the activation of PD123319-sensitive receptors and subsequent vasodilation, which can cause reduced peripheral resistance and even venous return.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which the heterodimers function are diverse. The AT 1 R-AT 2 R inhibitory interaction requires PKC-dependent AT 2 R phosphorylation (416). The AT 1 Rapelin receptor interaction inhibits AT 1 R ANG II binding (966).…”
Section: At 1 R-gpcr Heterodimermentioning
confidence: 99%